Análise retrospectiva dos atendimentos realizados no Serviço de Diagnóstico de Zoonoses da UNESP/ Botucatu entre 2016 e 2024 - Santos, Thiago Araujo dos [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The generation and analysis of data related to the occurrence of diseases in animals shows what is fundamental in responding to problems related to “One Health”. The aim of the study was to carry out a retrospective analysis of care provided at the Animal Infectious Diseases Service and the Zoonosis Diagnosis Service of the Veterinary Hospital (VH) of the School of Veterinary Medicine and Animal Science (FMVZ) of the São Paulo State University “Júlio de Mesquita Filho” (UNESP), Botucatu Campus, SP between the years 2016 and 2024. Frequency and geographic distribution analyzes were carried out diagnoses performed in the institution focusing on positive cases. The main conditions evaluated in the study were: leishmaniasis, toxoplasmosis, leptospirosis and rabies. The study suggests a seasonal trend for leptospirosis diagnoses, the same was not observed for other conditions. No trends were observed in relation to the sex of the animals considered in the study. The distribution of positive cases in the urban perimeter of the municipality of Botucatu showed an increase in the density of cases in some regions of the municipality, based on toxoplasmosis and leptospirosis. Epidemiological studies work for a better understanding of the health situation of a population and thus allow public authorities to draw lines for solving these problems.

A geração e análise de dados relativos à ocorrência de enfermidades em animais, se mostra mais do que fundamental na resposta de problemas relacionados à “Uma só saúde”. O estudo teve como objetivo realizar análise retrospectiva dos atendimentos realizados no Serviço de Enfermidades Infecciosas dos Animais e Serviço de Diagnóstico de Zoonoses do Hospital Veterinário (HV) da Faculdade de Medicina Veterinária e Zootecnia (FMVZ) da Universidade Estadual Paulista “Júlio de Mesquita Filho” (UNESP), Campus de Botucatu, SP entre os anos de 2016 e 2024. Foram realizadas análises de frequência e distribuição geográfica dos diagnósticos realizados na instituição com foco nos casos reagentes. As principais afecções avaliadas no estudo foram: leishmaniose, toxoplasmose, leptospirose e raiva. O estudo sugere uma tendência sazonal para os diagnósticos de leptospirose, o mesmo não foi observado para as outras afecções. Não foram observadas tendências em relação ao sexo dos animais considerados no estudo. A distribuição dos casos reagentes no perímetro urbano do município de Botucatu evidenciou aumento na densidade de casos em algumas regiões do município, no caso da toxoplasmose e leptospirose. Estudos epidemiológicos favorecem a melhor compreensão da situação em saúde de uma população e assim permitir ao poder público traçar linhas para a solução desses problemas
Retrospective analysis of diagnostics provided at the Zoonoses Diagnosis Service at UNESP/ Botucatu between 2016 and 2024
Keywords: Zoonoses; Epidemiologia; Geoprocessamento; Vigilância epidemiológica; Zoonosis; Epidemiology; Geoprocessing; Epidemiological surveillance